Kajian Etnobotani Tumbuhan Sagu (Metroxylon spp. Arecaceae) Pada Masyarakat Desa Radda Kecamatan Baebunta Kabupaten Luwu Utara Provinsi Sulawesi Selatan - Syahdima Syahdima; Eny Yuniati; Ramadhanil Ramadhanil (Biocelebes, 2013)
Research on the study of ethnobotany plants sago (Metroxylon spp Palma) in the community at the village of Radda, District of Baebunta, Regency of North Luwu, Province of South Sulawesi have been implemented. The goal of this research was to know the uses of sago in the daily life, how it was used, which part of this plant can be used and how the traditional taxonomy of North Luwu’s community. The method of this research was descriptive methode with Qualitative and Quantitative by using of semi structural interview and open ended. sampling the plants sago through exploration. Sago plant utilization data collection performed by the method of indept interview with respondents, the number of respondents by as much as 10 percent of total hosehold. The results obtained was sago plants can be used as foodstuffs (26,59%), medicines (14,11%), construction materials (26,59%), indigenous rituals (9,18%) and many more other utilization of the sago plants (23,52%) is the roots used as bullets or shots toys that usually called the “baladuk” and it can be use as doormat, in addition to the roots, the leaves of sago can be uses to packing the sago plants it self, wrapping griled fish, wrapping the cake and many more. Where as mucus sago was used as glue, the dregs of the sago plants used for fodder and used as fertilizer. Organ which is root (1,42%), bar (32,1%), leaf (32,1%), flower (0,28%), frond (30,7%), frond skin (3,4%), fruit (0%) and (0%). For taxonomy traditional called “Tabaro”. Key words: Ethnobotany, Metroxylon spp., Village Radda.